Anxiety, depression, and other related factors in Turkish pregnant women during the COVID-19 pandemic's first wave: A cross-sectional and web-based study - Filiz Aslantekin-Özcoban; Sibel Peksoy-Kaya (National Scientific Medical Center, 2022)
Aim: This research aims to determine attitudes, behaviors, anxiety and depression levels of pregnant women regarding the prevention measures from the COVID-19 pandemic. Material and methods: The cross-sectional study population consists of pregnant women (N=1008) in Turkey. Data were collected with Information Form, Hospital Anxiety and Depression Scale. Results: Anxiety score was 8 and above in 63.6% of the pregnant women while that of depression was 8 and above in 52.1% of them. There was an increase in risk of anxiety in pregnant women regarding the items about family and loved ones being infected by COVID-19 2.36 times, and about the baby being infected and lost 2.61 times. This rate increased 1.60 times in those who could not have screening tests due to pandemic, and 1.40 in those whose frequency of attending antenatal controls decreased. Risk of depression, on the other side, increased 1.59 times in those who were anxious about not receiving any companion support at birth, 1.65 times in those who couldn't have screening tests due to the pandemic, 1.38 times in those who didn't plan the place to give birth and didn't learn its conditions, and 1.55 times whose frequency of attending antenatal controls decreased. Conclusion: It has been determined that psychosocial support services and antenatal care may be regarded as fundamental fields of intervention.